Japan’s banking crisis: An event-study perspective - Miyajima, Hideaki; Yafeh, Yishay (Journal of Banking & Finance, 2007)
We calculate abnormal stock returns for Japanese non-financial companies around major events associated with the banking crisis (1995–2000), and find that not all companies were equally sensitive to the malaise of the banking sector: the most affected were small, leveraged, low-tech companies with low credit ratings and low market to book ratios. This is consistent with “credit crunch” theories (companies with limited access to financial markets are sensitive to changes in bank lending) and with claims that innovation is rarely financed by bank debt. We do not find much evidence on the alleged misallocation of loans to support ailing bank clients.